In Medias Res Peter Sloterdijk's Spherological Poetics of Being - Schinkel, Willem (Amsterdam University Press, 2011)
Sloterdijk has in recent years grown into one of Germany's most influential thinkers. His work, which is extremely relevant for philosophers, scientists of art and culture, sociologists, political scientists and theologists, is only now gradually being translated in English. This book makes his work accessible to a wider audience by putting it to work in orientation towards current issues. Sloterdijk's philosophy moves from a Heideggerian project to think 'space and time' to a Diogenes-inspired 'kynical' affirmation of the body and a Deleuzian ontology of network-spheres. In a range of accessible and clearly written chapters, this book discusses the many aspects of this thought.